[Math] Convert recursive formula to explicit formula using backtracking

recurrence-relations

This is a question from the book Discrete Mathematical Structures by Bernard Kolman, Robert C. Busby and Sharon Cutler Ross.

I want to find the explicit formula of the following recursive formula using backtracking: $$C_n = C_{n-1} + n$$

The initial condition is $c_1 = 4$.

  1. $C_n = C_{n-1} + n$

    $C_{n-1} = C_{(n-1)-1} = C_{n-2} + n$

  2. $C_n = C_{n-2} + n + n$

    $C_{n-2} = C_{(n-2)-1} = C_{n-3} + n$

  3. $C_n = C_{n-3} + n + n + n$

$$\therefore C_n = C_{n-(n-1)} + n(n-1)$$
$$= C_1 + n^2 – n$$
$$= n^2 – n + 4$$

However, the answer in the book is $3 + \frac{n(n+1)}{2}$

Edit: I was wrongly substituting. I corrected the error but I am still not getting the answer.

  1. $C_n = C_{n-1} + n$

    $C_{n-1} = C_{(n-1)-1} + (n-1) = C_{n-2} + n – 1$

  2. $C_n = C_{n-2} + n – 1 + n = C_{n-2} + 2n – 1$

    $C_{n-2} = C_{(n-2)-1} + (n – 2) = C_{n-3} + n – 2$

  3. $C_n = C_{n-3} + n – 2 + 2n – 1 = C_{n-3} + 3n – 3$

0, 1, 3, … are triangular numbers.

$$\therefore C_n = C_{n-(n-1)} + n(n-1) – \frac{n(n+1)}{2}$$

Simplifying this does not give the answer. Where is the mistake?

Best Answer

$$C_n = C_{n-1} + n = (C_{n-2} + n-1) + n = C_{n-3} + (n-2) + (n-1) + n = \dots = C_1 + 2 + 3 + \dots + n = 4 + 2 + 3 + \dots + n = 3 + (1 + 2 + 3 + \dots + n) = 3 + \frac {n(n+1)} 2 .$$

Alternatively, you may note that

$$C_n - C_1 = (C_n - C_{n-1}) + (C_{n-1} - C_{n-2}) + \dots + (C_2 - C_1) = n + (n-1) + \dots + 2 = \frac {n (n+1)} 2 - 1,$$

whence $C_n = C_1 - 1 + \frac {n (n+1)} 2 = 3 + \frac {n (n+1)} 2$.

Related Question